A multicenter investigation of the hemodynamic effects of induction agents for trauma rapid sequence intubation. Issue 6 (June 2021) - Leede, Emily; Kempema, James; Wilson, Chad; Rios Tovar, Alejandro J.; Cook, Alan; Fox, Erin; Regner, Justin; Richmond, Robyn; Carrick, Matt; Brown, Carlos V.R.
Abstract : BACKGROUND: Several options exist for induction agents during rapid sequence intubation (RSI) in trauma patients, including etomidate, ketamine, and propofol. These drugs have reported variable hemodynamic effects (hypotension with propofol and sympathomimetic effects with ketamine) that could affect trauma resuscitations. The purpose of this study was to compare the hemodynamic effects of these three induction agents during emergency department RSI in adult trauma. We hypothesized that these drugs would display a differing hemodynamic profile during RSI. METHODS: We performed a retrospective (2014–2019), multicenter trial of adult (≥18 years) trauma patients admitted to eight ACS-verified Level I trauma centers who underwent emergency department RSI. Variables collected included systolic blood pressure (SBP) and pulse before and after RSI. The primary outcomes were change in heart rate and SBP before and after RSI. RESULTS: There were 2, 092 patients who met criteria, 85% received etomidate (E), 8% ketamine (K), and 7% propofol (P). Before RSI, the ketamine group had a lower SBP (E, 135 vs. K, 125 vs. P, 135 mm Hg, p = 0.04) but there was no difference in pulse (E, 104 vs. K, 107 vs. P, 105 bpm, p = 0.45). After RSI, there were no differences in SBP (E, 135 vs. K, 130 vs. P, 133 mm Hg, p = 0.34) or pulse (E, 106 vs. K, 110 vs. P, 104 bpm, p = 0.08). There was no difference in the average change of SBP (E, 0.2 vs. K, 5.2 vs. P, −1.8 mm Hg, p = 0.4) or pulse (E, 1.7 vs. K, 3.5 bpm vs. P, −0.96, p = 0.24) during RSI. CONCLUSION: Contrary to our hypothesis, there was no difference in the hemodynamic effect for etomidate versus ketamine versus propofol during RSI in trauma patients. LEVEL OF EVIDENCE: Therapeutic, Level IV.